2004
DOI: 10.1074/jbc.m311608200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxygen and Light Intensity on Transcriptome Expression in Rhodobacter sphaeroides 2.4.1

Abstract: The roles of oxygen and light on the regulation of photosynthesis gene expression in Rhodobacter sphaeroides 2.4.1 have been well studied over the past 50 years. More recently, the effects of oxygen and light on gene regulation have been shown to involve the interacting redox chains present in R. sphaeroides under diverse growth conditions, and many of the redox carriers comprising these chains have been well studied. However, the expression patterns of those genes encoding these redox carriers, under aerobic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 90 publications
6
73
0
Order By: Relevance
“…We and others have shown that changes in the R. sphaeroides transcriptome correlate well with the metabolic and physiological changes occurring in this bacterium (38,44). To ensure that the observed responses are stimulus specific, we used H 2 O 2 concentrations that do not severely impair cellular survival and growth.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have shown that changes in the R. sphaeroides transcriptome correlate well with the metabolic and physiological changes occurring in this bacterium (38,44). To ensure that the observed responses are stimulus specific, we used H 2 O 2 concentrations that do not severely impair cellular survival and growth.…”
Section: Resultsmentioning
confidence: 99%
“…The wild-type was grown under five different growth conditions and the two mutant strains under one growth condition, a total of seven experiments. All strains, described in detail below, were grown as independent triplicate cultures (Roh et al, 2004). RNA was harvested from each culture, converted to cDNA, then applied to its own microarray chip.…”
Section: Methodsmentioning
confidence: 99%
“…A previously described RNA isolation procedure (Roh & Kaplan, 2002) was modified to optimize the isolation of intact mRNA for microarray analysis (Roh et al, 2004). We modified the earlier procedure by eliminating cell collection by centrifugation.…”
mentioning
confidence: 99%
“…In the case of the most studied purple photosynthetic bacterium Rhodobacter sphaeroides, the LH complexes and RCs are only synthesized when the oxygen tension is below a critical value (11,12). Then if cells are grown at high light intensities, the PSU is dominated by LH1/RC core complexes (13,14).…”
mentioning
confidence: 99%